ANALYSIS OF NORMATIVE LEGAL DOCUMENTS ON THE PREVENTION OF ILLEGAL TURNOVER OF PYROTECHNICS IN ENSURING PUBLIC SAFETY - Tojaliyev Ilyasbek Lochinboy (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to evaluate the efforts of the Republic of Uzbekistan in addressing the illegal circulation of pyrotechnic devices, focusing on public safety and health concerns. Method: The research examines a comprehensive approach involving legislative, administrative, and enforcement measures, particularly the role of the National Guard and other state institutions. It analyzes regulations such as the 2021 amendments to the Criminal Code and the introduction of new licensing procedures. Results: The study finds that while there has been a reduction in pyrotechnic-related injuries, especially during New Year celebrations, illegal circulation continues to pose a significant threat. The National Guard's actions, including the seizure of over 3.5 million illegal devices, have shown some success, but challenges remain. Novelty: This research offers a unique analysis of Uzbekistan’s regulatory framework and its evolving measures to control pyrotechnics, highlighting the introduction of stricter penalties and enhanced safety protocols. The study underscores the need for continuous public awareness and better enforcement to further mitigate risks.